2008
DOI: 10.1590/s1413-86702008000500008
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis in hematopoietic stem cell transplant recipients: a retrospective analysis

Abstract: Invasive aspergillosis (IA) currently is an important cause of mortality in subjects undergoing hematopoietic stem cell transplants (HSCT) and is also an important cause of opportunistic respiratory and disseminated infections in other types of immunocompromised patients. We examined the medical records of 24 cases of proven and probable invasive aspergillosis (IA) at the Hospital de Clinicas of the Federal University of Parana, Brazil, from January 1996 to October 2006. During this period occurred a mean of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…In addition, the spectrum of the fungal microorganisms was also similar with the previous reports that showed Aspergillus spp as the most common agent. 5,7,9,16 The major limitation of this study is the failure to detect a causative microorganism in 37.5% of the patients, which was attributable to the difficulties in performing bronchoscopy on some of the patients due to the several contraindications such as respiratory distress and severe thrombocytopenia rendering a significant number of our patients as possible cases of IFIs. However, several authors indicated that diagnostic yield of bronchoscopy for FPIs is low and does not have a survival benefit in HSCT recipients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the spectrum of the fungal microorganisms was also similar with the previous reports that showed Aspergillus spp as the most common agent. 5,7,9,16 The major limitation of this study is the failure to detect a causative microorganism in 37.5% of the patients, which was attributable to the difficulties in performing bronchoscopy on some of the patients due to the several contraindications such as respiratory distress and severe thrombocytopenia rendering a significant number of our patients as possible cases of IFIs. However, several authors indicated that diagnostic yield of bronchoscopy for FPIs is low and does not have a survival benefit in HSCT recipients.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 Pulmonary involvement is the most common localization of IFIs during the course of HSCT. 7 Unfortunately, both the diagnosis and the therapy are a clinical dilemma as the diagnostic tools used for early and reliable diagnosis are often inadequate. A variety of fungal microorganisms are responsible for several diseases in HSCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aggressive medical interventions have allowed critically ill patients to survive longer, increasing their overall risk to acquire fungal infections. 5,12 In the present study, we showed the distribution of fi lamentous fungi causing invasive fungal diseases at the haematology unit of HCPA, a reference medical centre in Southern Brazil. Roughly, half of infections were caused by Aspergillus species, especially A. fumigatus and A. fl avus (the latter usually in association with invasive fungal rhinosinusitis).…”
Section: Discussionmentioning
confidence: 61%
“…The distribution of Aspergillus species causing IFD at Hospital de Clínicas da Universidade Federal do Paraná -another referral centre for allogeneic HSCT in Southern Brazil -was recently published. 12 A total of 24 cases of proven/probable IA were detected over a 10-year period in that investigation, including 11 proven IA cases. The reported incidence of 3% was probably underestimated, since galactomannan testing was not available at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Afteralongprocessandlargeamountsofclinicalpractice,it is now considered a novel therapeutic strategy benefiting patientswithvarioushematologicalmalignancies [1][2][3],solid malignancies [4], or inherited stem cell disorders [5][6][7]. In recentyears,therehasbeenagrowingnumberoflong-term recipients as the technique and quality of allo-HSCT is improving;however,thiscohortstillsuffersfromahighriskof potential late allo-HSCT complications, including the developmentofsecondaryneoplasms [8],graftversushostdisease (GVHD) [9], and infections [10]. With the introduction of newgenerationsofdrugsintoclinicalpractice,GVHDandinfections can be effectively prevented, controlled, and even cured.ApartfromGVHDandvariousinfections,donorcell leukemia(DCL),ahematologicaldisorderfirstlyreportedin 1971 [11],hasbeenfoundtobeemergingatahighfrequency inclinic.Untilnow,DCLwasawell-recognizeddiseaseentity occurringafterallo-HSCTmainlyduetooncogenictransformationofnormaldonorhematopoieticcellsintherecipient.…”
Section: Introductionmentioning
confidence: 99%